Dexmedetomidine preconditioning protects against lung injury in hemorrhagic shock rats - Zhang,Lei (2019)
Abstract Background and objectives: Dexmedetomidine has demonstrated protective effects against lung injury in vitro. Here, we investigated whether dexmedetomidine preconditioning protected against lung injury in hemorrhagic shock rats. Methods: Male Sprague-Dawley rats were randomly divided into four groups (n = 8): control group, hemorrhagic shock group, 5 ug.kg-1 dexmedetomidine (DEX1) group, and 10 ug.kg-1 dexmedetomidine (DEX2) group. Saline or dexmedetomidine were administered over 20 min. 30 min after injection, hemorrhage was initiated in the hemorrhagic shock, DEX1 and DEX2 group. Four hours after resuscitation, protein and cellular content in bronchoalveolar lavage fluid, and the lung histopathology were measured. The malondialdehyde, superoxide dismutase, Bcl-2, Bax and caspase-3 were also tested in the lung tissue. Results: Compare with hemorrhagic shock group, 5 ug.kg-1 dexmedetomidine pretreatment reduced the apoptosis (2.25 ± 0.24 vs. 4.12 ± 0.42%, p < 0.05), histological score (1.06 ± 0.12 vs. 1.68 ± 0.15, p < 0.05) and protein (1.92 ± 0.38 vs. 3.95 ± 0.42 mg.mL-1, p < 0.05) and WBC (0.42 ± 0.11 vs. 0.92 ± 0.13 × 109/L, p < 0.05) in bronchoalveolar lavage fluid. Which is correlated with increased superoxide dismutase activity (8.35 ± 0.68 vs. 4.73 ± 0.44 U.mg-1 protein, p < 0.05) and decreased malondialdehyde (2.18 ± 0.19 vs. 3.28 ± 0.27 nmoL.mg-1 protein, p < 0.05). Dexmedetomidine preconditioning also increased the Bcl-2 level (0.55 ± 0.04 vs. 0.34 ± 0.05, p < 0.05) and decreased the level of Bax (0.46 ± 0.03 vs. 0.68 ± 0.04, p < 0.05), caspase-3 (0.49 ± 0.03 vs. 0.69 ± 0.04, p < 0.05). However, we did not observe any difference between the DEX1 and DEX2 groups for these (p > 0.05). Conclusion: Dexmedetomidine preconditioning has a protective effect against lung injury caused by hemorrhagic shock in rats. The potential mechanisms involved are the inhibition of cell death and improvement of antioxidation. But did not show a dose-dependent effect.